Development of Information Management System for Special Lecturers and Study Visits for Students of the Faculty of Physical Education Srinakharinwirot University to Increase Financial Efficiency - Traiwech, Jinda; Panprasert, Chariwan; Poonsawat, Chaonk (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2025)
The aim of this research was to develop and evaluate an information management system for special instructors and study visits for the Faculty of Physical Education at Srinakharinwirot University. The system consisted of five processes: 1) license information management 2) special instructor and study visit information management 3) approval status checking 4) document creation and 5) data reporting. The purpose of the system was to increase the financial efficiency of reimbursement for special instructors' compensation and expenses for study visits by making the process more systematic and timely. The system relied on information technology to help executives and related parties make more informed decisions. The evaluation results showed that the use of the system was at a very good level, indicating that it can effectively increase financial efficiency.